Evaluating BOS Fund Policy in Merdeka Belajar Discourse: A Systemic Functional Linguistics Analysis: Penelitian - Muhammad Tahir; Andi Sahtiani Jahrir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education policy is not only an administrative instrument, but also a discourse to legitimize reform, persuade stakeholders, and build accountability. In Indonesia, the Merdeka Belajar initiative marked a major shift in education governance, with Episode 3 focusing on the distribution of BOS funds. While previous research has highlighted the financial and governance aspects, few have addressed the discourse dimension. This study fills this gap by applying Systemic Functional Linguistics (SFL) to the minister's speech launching Merdeka Belajar Episode 3. Analysis based on Halliday's metafunctional framework focused on the use of conjunctions as cohesive devices. The findings reveal three main rhetorical orientations: (1) expansion through additive conjunctions (and, or) that present the reform as comprehensive; (2) justification through causal conjunctions (because, so, in order that) that rationalize the policy as imperative; and (3) legitimation through projection (that) that presents an authoritative voice to strengthen institutional credibility. This pattern confirms that language choices serve an ideological function by portraying BOS reform as inclusive, rational, and accountable. By comparing the Indonesian case with studies of policy discourse in Australia, Europe, China, and the US, this research contributes to the global debate on the language and legitimacy of reform.